THE FIXED-TERM EMPLOYMENT CONTRACT IN GERMANY AND RUSSIA: COMPARATIVE LEGAL ASPECTS - О. В., Чесалина; Л. А., Чиканова; А., Шаррер (Teisė, 2016)
The article comparatively analyzes current labour legislation and court decisions in the Federal Republic of Germany and in the Russian Federation related to fixed-term employment contracts. In particularly the sources of regulation of fixed-term employment contracts are analyzed. Furthermore the cases, in which it is permitted to conclude a fixed-term employment contract due to a justifying reason and the exceptions to this rule as well as the required form of fixed-term employment contracts in both countries are examined. The possibilities for prolongation and termination of fixed-term employment contracts are comparatively analyzed. Finally the requirements and the prodecure for settling individual labour disputes relating to fixed-term employment contracts are compared.